Exhaust gas purification catalyst for saddle-type vehicles
By using a single-layer catalyst structure in the exhaust gas purification catalyst of two-wheeled motor vehicle and combining Rh and Pd-loaded composite catalyst particles, the problems of poor purification performance and high cost in the prior art are solved, and the high temperature and fuel-rich atmosphere are realized Excellent purification performance and economicality.
Patent Information
- Application Number
- CN202180069397.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-15
- Filing Date
- 2021-12-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-12-14
AI Technical Summary
In the prior art, the exhaust gas purification catalyst for two-wheeled motor vehicles has poor purification performance in high temperature and fuel-rich atmospheres, and is costly, and has problems such as Ce supply crisis and price fluctuations.
Using a single-layer catalyst structure, by combining Rh-supported composite catalyst particles and Pd-supported composite catalyst particles, a single-layer catalyst layer on a metal substrate is formed, including zirconia-based and alumina-based composite catalyst particles, and Rh is supported in the catalyst layer. and metal components such as Pd.
Excellent purification performance under high temperature and fuel-rich atmosphere is achieved, production costs are reduced, excessive use of Ce is avoided, and is suitable for two-wheeled vehicles with small capacity engines.
Smart Images

Figure CN116322946B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an exhaust gas purifying catalyst for a saddle-riding type vehicle such as a motorcycle and a method for producing the same, and more particularly to an exhaust gas purifying catalyst for a saddle-riding type vehicle in which a catalyst layer is formed of only one layer. Background Art
[0002] The exhaust gas of gasoline-fueled automobiles and two-wheeled vehicles contains harmful components such as hydrocarbons (HC), carbon monoxide (CO), and nitrogen oxides (NOx). In order to purify them, it is necessary to use a catalyst to purify various harmful components, that is, to oxidize hydrocarbons (HC) and convert them into water and carbon dioxide, oxidize carbon monoxide (CO) and convert them into carbon dioxide, and reduce nitrogen oxides (NOx) and convert them into nitrogen, etc. As a catalyst for treating such exhaust gas (hereinafter referred to as "exhaust gas purification catalyst"), a three-way catalyst (Three-Way Catalyst: TWC) that can oxidize and reduce CO, HC, and NOx is used. As such a three-way catalyst, for example, the following three-way catalyst is widely known: a three-way catalyst obtained by loading platinum group metals (PGM: Platinum Group Metal) such as ruthenium, rhodium, palladium, osmium, iridium, and platinum on alumina base material particles having a high specific surface area as catalytically active components, and loading it on a substrate, such as a monolithic substrate of a refractory ceramic or metal honeycomb structure.
[0003] As for the internal combustion engines of the above-mentioned automobiles, the ratio of fuel to air (air-fuel ratio, A / F) varies greatly according to the operating conditions of the engine such as acceleration, deceleration, low-speed driving, and high-speed driving. With the theoretical air-fuel ratio of 14.7 in the exhaust gas as the boundary, the oxygen excess atmosphere (lean fuel atmosphere) in which the oxidation reaction becomes favorable and the fuel excess condition (rich fuel atmosphere) in which the reduction reaction becomes favorable appear alternately and repeatedly according to the driving conditions. Therefore, the exhaust gas catalyst needs to exert a certain catalytic performance under any conditions in the lean fuel atmosphere and the rich fuel atmosphere. Especially in the case of two-wheeled motor vehicles, there is a tendency to increase the engine speed in a rich fuel atmosphere to drive in order to increase the output power, so it is required to exert excellent catalytic performance in a rich fuel atmosphere. Therefore, the air-fuel ratio (A / F) has been controlled all the time, but the catalyst cannot fully exert the purification catalytic performance by controlling the air-fuel ratio (A / F) alone, so the catalyst layer itself is also required to control the air-fuel ratio (A / F).
[0004] Therefore, in order to prevent the reduction of the purification performance of the catalyst caused by the change of the air-fuel ratio by utilizing the chemical action of the catalyst itself, a catalyst using a co-catalyst and a platinum group element as a catalytically active component is used. As such a co-catalyst, a co-catalyst (hereinafter sometimes referred to as "OSC material") having an oxygen storage capacity (OSC) that releases oxygen in a reducing atmosphere and absorbs oxygen in an oxidizing atmosphere is known. Specifically, ceria (cerium oxide, CeO2), ceria-zirconia composite oxides, etc. are known as OSC materials having oxygen storage capacity. These OSC materials function as a buffer to reduce the changes in the oxidizing and reducing properties of the exhaust gas, and have the function of maintaining the purification performance of the catalyst. In addition, the oxygen storage capacity (OSC) of the ceria-zirconia composite oxide obtained by dissolving zirconium oxide in ceria is more excellent, so it is added to many catalysts as an OSC material.
[0005] However, the exhaust gas purification catalyst for two-wheeled motor vehicles has special issues different from those for four-wheeled vehicles. For example, compared with the exhaust gas purification catalyst for four-wheeled vehicles, the exhaust gas purification catalyst for two-wheeled motor vehicles has limited space for mounting the catalyst, so it is required to exert a high purification capacity even with a small capacity. In addition, the exhaust gas flow path of two-wheeled motor vehicles is relatively short, and there is a tendency to use a large amount of fuel in order to attach importance to output power, so the catalyst is easily exposed to high temperature. And, correspondingly, the oxygen concentration in the exhaust gas decreases, so there is a tendency for the air-fuel ratio (A / F) in the exhaust gas to become less than the theoretical air-fuel ratio of 14.7. Therefore, it is required to have excellent heat resistance and excellent exhaust gas purification efficiency even in a fuel-rich atmosphere with an air-fuel ratio (A / F) of less than 14.7.
[0006] For example, Patent Document 1 discloses a catalyst material for purifying exhaust gas from an internal combustion engine, characterized in that it comprises a carrier formed of a cerium-zirconium composite oxide (wherein the amount of CeO2 is 45 to 70 mass %, the amount of ZrO2 is 20 to 45 mass %, the amount of Nd2O3 is 2 to 20 mass %, and the amount of La2O3 is 1 to 10 mass %), and a catalyst component comprising metal Pd or Pd oxide loaded on the carrier.
[0007] In addition, Patent Document 2 discloses an exhaust gas purification catalyst for a saddle-type vehicle, characterized in that it has a first catalyst layer formed on the surface of a carrier formed of a ceramic or metal material, and a second catalyst layer formed on the first catalyst layer, the first catalyst layer having a carrier formed of a cerium-zirconium composite oxide (wherein the amount of CeO2 is 45 to 70% by mass, the amount of ZrO2 is 20 to 45% by mass, the amount of Nd2O3 is 2 to 20% by mass, and the amount of La2O3 is 1 to 10% by mass), and a catalyst layer loaded on the carrier. The catalyst component is metal Pd or Pd oxide, and the second catalyst layer has a carrier formed by a zirconium-based composite oxide (wherein the amount of ZrO2 is 50-95% by mass, the amount of CeO2 is 0-40% by mass, the amount of Nd2O3 is 2-20% by mass, and the amount of La2O3 is 1-10% by mass), and a catalyst component containing metal Rh or Rh oxide supported on the carrier, or has the aforementioned carrier, a catalyst component containing metal Rh or Rh oxide supported on the carrier, and a catalyst component containing metal Pt or Pt oxide.
[0008] On the other hand, as a catalyst that achieves low cost by not using relatively expensive precious metals such as Pt and Rh, Patent Document 3 discloses a palladium catalyst for exhaust gas from a saddle-type vehicle, which is an exhaust gas purification catalyst for a saddle-type vehicle arranged in the exhaust passage of an internal combustion engine, the palladium catalyst comprises a substrate and a catalyst layer as a single layer, the catalyst layer contains palladium as a catalytically active component, an inorganic porous body such as porous γ-alumina as a catalyst carrier, and cerium dioxide (CeO2) particles and barium as co-catalyst components.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2010-227739
[0012] Patent Document 2: WO2010 / 109734
[0013] Patent Document 3: Japanese Patent Application Publication No. 2013-208578 Summary of the invention
[0014] Problems to be solved by the invention
[0015] In the above-mentioned Patent Document 1, a catalyst material (Pd-loaded cerium-zirconium composite oxide) in which Pd is loaded on the surface of a cerium-zirconium composite oxide of a specific composition is used as a base material particle. However, this catalyst material alone still has insufficient purification performance (see Examples 1 and 2).
[0016] In addition, as for the exhaust gas discharged from the internal combustion engine of automobiles, a large amount of carbon monoxide (CO), hydrocarbons (HC), and nitrogen oxides (NOx) are discharged when the catalyst temperature is low, such as at startup. In order to improve the purification performance, it is important to increase the temperature of the catalyst early and improve the low-temperature purification performance of the catalyst. However, the catalyst material described in Patent Document 1 is still a material with insufficient low-temperature catalytic activity when it is alone (see Examples 1 and 2).
[0017] On the other hand, Ce, an important rare earth used in phosphors, glass substrate polishing agents, etc. in addition to catalyst materials, has been in a supply crisis due to the recent overseas situation, and its supply is extremely limited. In addition, there is a surge in international prices. Therefore, new catalyst materials with a small amount of Ce are required, but the catalyst material described in Patent Document 1 still uses a large amount of Ce, which does not meet the recent requirements from this point of view.
[0018] In addition, the exhaust gas purification catalyst described in Patent Document 2 has the following stacked structure: a first catalyst layer using Pd-loaded cerium-zirconium composite oxide described in Patent Document 1 as a catalyst component is provided on the surface of the substrate, and a second catalyst layer using Rh or Pt-loaded cerium-zirconium composite oxide as a catalyst component is further provided on the first catalyst layer. In order to provide more than two catalyst layers as described above, each catalyst layer requires a series of processes such as coating, calcination, loading, drying and calcination of the catalyst slurry, so the manufacturing cost increases, and as a result, the obtained exhaust gas purification catalyst becomes a high-cost catalyst. In addition, since the catalyst layer of the exhaust gas purification catalyst described in Patent Document 2 is a stacked structure, the gas diffusion is insufficient, and the purification performance and low-temperature catalytic activity are insufficient (see Tables 3 and 5).
[0019] On the other hand, Patent Document 3 describes an exhaust gas purification catalyst provided with a single-layer catalyst using a small amount of Ce, but the purification performance is extremely low (see Tables 2 and 3).
[0020] The present invention has been made in view of the above problems. That is, the object of the present invention is to provide an exhaust gas purification catalyst for a saddle-type vehicle which has a simple and low-cost structure with only one catalyst layer but has excellent purification performance of CO, HC, and NOx and their low-temperature purification performance.
[0021] Means for solving problems
[0022] The inventors of the present application conducted intensive research to solve the above-mentioned problems and found a single-layer catalyst using a combination of predetermined Rh-loaded composite catalyst particles and predetermined Pd-loaded composite catalyst particles, and found that the above-mentioned problems can be solved by using such a single-layer catalyst, thereby completing the present invention.
[0023] That is, the present invention provides various specific aspects shown below.
[0024] [1] An exhaust gas purification catalyst for a saddle-type vehicle, which is an exhaust gas purification catalyst for a saddle-type vehicle arranged in an exhaust gas passage of an internal combustion engine, the exhaust gas purification catalyst for a saddle-type vehicle comprising a metal substrate and a single-layer catalyst layer arranged on the metal substrate, the catalyst layer comprising: a first composite catalyst particle, the first composite catalyst particle having at least a zirconia-based matrix particle and Rh and CeO2 particles co-supported on the surface of the zirconia-based matrix particle; and a second composite catalyst particle and / or a third composite catalyst particle, the second composite catalyst particle comprising an alumina matrix particle and Pd supported on the surface of the alumina matrix particle, the third composite catalyst particle having at least a ceria-alumina matrix particle and Pd supported on the surface of the ceria-alumina matrix particle.
[0025] [2] The exhaust gas purification catalyst for a saddle-type vehicle according to [1], wherein the zirconia-based matrix particles are rare earth solid solution zirconia matrix particles in which at least one rare earth element selected from the group consisting of Ce, Nd and La is solid-solved.
[0026] [3] The exhaust gas purification catalyst for a saddle-type vehicle according to [1] or [2], wherein the zirconium oxide-based base material particles contain 65 to 85 mass % of ZrO 2 and 15 to 35 mass % of an oxide of a rare earth element in terms of oxide.
[0027] [4] The exhaust gas purification catalyst for a saddle-type vehicle according to any one of [1] to [3], wherein the second composite catalyst particles include the alumina base material particles and Pd and Ba supported on the surface of the alumina base material particles.
[0028] [5] The exhaust gas purification catalyst for a saddle-type vehicle as described in any one of [1] to [4], wherein the ceria alumina matrix particles of the third composite catalyst particles contain 70 to 90% by mass of Al2O3 and 10 to 30% by mass of CeO2 in terms of oxides.
[0029] [6] The exhaust gas purification catalyst for a saddle-type vehicle according to any one of [1] to [5], wherein the catalyst layer further contains fourth composite catalyst particles, the fourth composite catalyst particles comprising ceria alumina matrix particles and Rh supported on the surface of the ceria alumina matrix particles.
[0030] [7] The exhaust gas purification catalyst for a saddle-rider type vehicle according to any one of [1] to [6], wherein the coating amount of the catalyst layer is 1 to 200 g / L per 1 L of the metal substrate.
[0031] Effects of the Invention
[0032] According to the present invention, a high-performance exhaust gas purification catalyst for saddle-type vehicles can be realized. Although it is a simple and low-cost structure with only one catalyst layer, it has excellent purification performance of CO, HC, and NOx and their low-temperature purification performance, and excellent productivity and economy. Moreover, the exhaust gas purification catalyst for saddle-type vehicles of the present invention can be particularly suitably used as a three-way catalyst (TWC: Three Way Catalyst) for reducing NOx, CO, HC, etc. in exhaust gas based on its composition and structure. In particular, the exhaust gas purification catalyst for saddle-type vehicles of the present invention can be preferably used in the field of two-wheeled vehicles that are small in capacity and require high heat resistance, and also require high exhaust gas purification efficiency in a fuel-rich atmosphere. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] [ Figure 1 ] is a schematic cross-sectional view showing an exhaust gas purification catalyst 100 for a saddle-type vehicle according to an embodiment.
[0034] [ Figure 2 ] is a schematic cross-sectional view showing a schematic structure of the first composite catalyst particle 31.
[0035] [ Figure 3 ] is a schematic cross-sectional view showing a schematic structure of the second composite catalyst particle 41.
[0036] [ Figure 4 ] is a schematic cross-sectional view showing a schematic structure of the third composite catalyst particle 51.
[0037] [ Figure 5 ] is a schematic cross-sectional view showing a schematic structure of the fourth composite catalyst particle 61.
[0038] [ Figure 6 ] is a graph showing the purification performance (C450 purification rate) of the embodiment and the comparative example.
[0039] [ Figure 7 ] is a graph showing the low-temperature purification performance (T50) of the embodiment and the comparative example. DETAILED DESCRIPTION
[0040] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. However, the following embodiments are examples for illustrating the present invention, and the present invention is not limited thereto. That is, the present invention can be implemented with arbitrary changes without departing from the gist thereof. It should be noted that, in this specification, the expression of a numerical range such as "1 to 100" includes both its lower limit "1" and its upper limit "100". The expression of other numerical ranges is the same. In addition, in this specification, unless otherwise specified, the positional relationship such as up, down, left, and right is based on the positional relationship shown in the accompanying drawings. In addition, the dimensional ratios of the accompanying drawings are not limited to the ratios shown in the drawings.
[0041] Figure 1 : is a schematic cross-sectional view showing an exhaust gas purification catalyst 100 for a saddle-type vehicle according to the present embodiment. Figures 2 to 5 It is a schematic cross-sectional view showing the schematic structure of the first composite catalyst particle 31 , the second composite catalyst particle 41 , the third composite catalyst particle 51 , and the fourth composite catalyst particle 61 .
[0042] The exhaust gas purification catalyst 100 for a saddle-type vehicle of the present embodiment is characterized in that it comprises a metal substrate 11 and a single-layer catalyst layer 21 provided on the metal substrate 11, wherein the catalyst layer 21 contains first composite catalyst particles 31, and second composite catalyst particles 41 and / or third composite catalyst particles 51. The exhaust gas purification catalyst 100 for a saddle-type vehicle of the present embodiment is provided in an exhaust gas passage of an internal combustion engine, and purifies carbon monoxide (CO), hydrocarbons (HC), nitrogen oxides (NOx), etc. passing through the system.
[0043] The metal substrate 11 is a support for supporting the above-mentioned single-layer catalyst layer 21. As the metal substrate 11, a metal substrate known in the industry can be appropriately selected, and its type is not particularly limited. As the metal substrate 11, for example, a metal honeycomb carrier made of stainless steel, a wire mesh carrier made of stainless steel, a steel wool-like knitted fabric (knitwire) carrier, etc. can be cited, but it is not particularly limited thereto. In addition, its shape is not particularly limited, for example, any shape such as a prism, a cylinder, a sphere, a honeycomb, a sheet, a pellet, etc. can be selected. These shapes can be used alone, or two or more can be used in appropriate combinations.
[0044] The catalyst layer 21 is a single catalyst layer provided on the metal substrate 11. The catalyst layer 21 includes first composite catalyst particles 31, second composite catalyst particles 41 and / or third composite catalyst particles 51, and further includes fourth composite catalyst particles 61 as required.
[0045] The first composite catalyst particle 31 is a composite particle having at least a zirconia-based matrix particle 32, and Rh and CeO2 particles 33 co-supported on the surface 32a of the zirconia-based matrix particle 32. In the first composite catalyst particle 31, Rh and CeO2 particles 33 are co-supported on the surface 32a of the zirconia-based matrix particle 32, thereby suppressing the reduction of catalytic activity due to the growth of Rh particles, and for the exhaust gas of a saddle-type vehicle in which the concentration of carbon monoxide (CO), hydrocarbons (HC), and nitrogen oxides (NOx) changes sharply, the CeO2 particles 33 are supported to exert high purification performance with a wide A / F window, and the low-temperature purification performance is also improved. It should be noted that the first composite catalyst particle 31 can be used alone or in combination of two or more.
[0046] The zirconia-based matrix particles 32 are zirconium oxide (ZrO2), or a composite oxide obtained by doping other elements in zirconium oxide (ZrO2), or a solid solution thereof. Specific examples of the zirconia-based matrix particles 32 include zirconium oxide (IV), zirconium-rare earth element composite oxides, zirconium-transition element composite oxides, zirconium-rare earth element-transition element composite oxides, and the like. Here, the rare earth element is not particularly limited, and cerium, neodymium, praseodymium, lanthanum, yttrium, and the like can be mentioned. Rare earth elements can be used alone or in combination of two or more. When rare earth elements are included, the content ratio is not particularly limited, and the total amount converted to the oxide of the rare earth element (for example, La2O3, Nd2O3, Pr5O 11 In addition, as transition elements, there are no particular limitations, and examples thereof include chromium, cobalt, iron, nickel, titanium, manganese, and copper. One transition element may be used alone, or two or more transition elements may be used in combination as appropriate. In the case where transition elements are included, the content ratio thereof is not particularly limited, and relative to the total amount of the zirconium oxide matrix particles 32, the total amount converted by the oxides of the above transition elements (e.g., the sum of Fe2O3, TiO2, etc.) is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 0.5% by mass or more, preferably 10% by mass or less, more preferably 5% by mass or less, and further preferably 3% by mass or less. It should be noted that one zirconium oxide matrix particles 32 may be used alone, or two or more transition elements may be used in combination as appropriate.
[0047] As the zirconia-based matrix particle 32, a zirconia-based composite oxide containing 65 to 85 mass % of ZrO2 and 15 to 35 mass % of oxides of rare earth elements in terms of oxide conversion is preferred, and a zirconia-based composite oxide containing 70 to 80 mass % of ZrO2 and 20 to 30 mass % of oxides of rare earth elements in terms of oxide conversion is more preferred.
[0048] It should be noted that in the zirconium oxide-based matrix particles 32, a portion of zirconium can be replaced by alkali metal elements such as lithium, sodium, potassium, beryllium, magnesium, calcium, strontium, barium, and other alkaline earth metal elements. In addition, the alkali metal elements and alkaline earth metal elements can be used alone, or in any combination and ratio of two or more. In addition, the zirconium oxide-based matrix particles 32 may also contain hafnium (Hf) as an inevitable impurity, which is usually contained in zirconium oxide ore in an amount of about 1 to 2 mass%.
[0049] The average particle size D of the zirconia-based matrix particles 32 50 The average particle size D of the zirconia matrix particles 32 can be appropriately set according to the desired performance and is not particularly limited. 50 It is preferably 1 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, preferably 30 μm or less, more preferably 20 μm or less, further preferably 15 μm or less. It should be noted that in this specification, the average particle size D of the particles is 50 It refers to the median diameter measured by a laser diffraction particle size distribution analyzer (for example, laser diffraction particle size distribution analyzer SALD-3100 manufactured by Shimadzu Corporation).
[0050] Rh and CeO2 particles 33 are co-loaded on the surface 32a of the zirconium oxide-based matrix particles 32 in a highly dispersed manner. Here, Rh functions as a catalytically active component, and CeO2 particles 33 function as a catalytically active component or a co-catalyst having oxygen storage capacity (OSC: Oxygen Storage Capacity). By co-loading Rh and CeO2 particles 33 on the surface 32a of the zirconium oxide-based matrix particles 32, it is possible to improve heat resistance and suppress the reduction in catalytic performance when exposed to high temperatures, thereby improving purification performance and low-temperature purification performance. In addition, since CeO2 particles 33 are loaded on the surface 32a of the zirconium oxide-based matrix particles 32, the interaction between Rh and Ce is promoted, thereby also improving purification performance and low-temperature purification performance.
[0051] The content ratio of Rh can be appropriately set in consideration of the raw material, pore diameter, etc. of the zirconia-based matrix particles 32 and in accordance with the desired performance, and is not particularly limited. However, from the viewpoint of catalytic activity, etc., the total content of Rh is preferably 0.001 to 5% by mass, more preferably 0.01 to 3% by mass, and even more preferably 0.1 to 1% by mass, calculated as metal Rh, relative to the total amount of the first composite catalyst particles 31.
[0052] The content ratio of CeO2 particles 33 can be appropriately set according to the desired performance in consideration of the raw material, pore size, etc. of the zirconia-based matrix particles 32, and is not particularly limited. However, from the perspective of catalytic activity, etc., the content ratio is preferably 5 to 20 mass %, more preferably 7 to 18 mass %, and further preferably 10 to 15 mass % relative to the total amount of the first composite catalyst particles 31 (excluding the amount of precious metals) in terms of oxide conversion.
[0053] The second composite catalyst particles 41 are composite particles having at least alumina base material particles 42 and Pd supported on the surfaces 42a of the alumina base material particles 42. The second composite catalyst particles 41 may be used alone or in combination of two or more.
[0054] The alumina matrix particles 42 are matrix particles containing alumina (Al2O3) as a main component. Here, the so-called "containing alumina as a main component" means that the alumina is contained in an amount greater than 90% by mass and less than 100% by mass relative to the total amount of the alumina matrix particles 42. Specific examples of the alumina matrix particles 42 include, for example, alumina, silica-alumina, aluminosilicates, alumina-zirconia, alumina-chromia, alumina-ceria, alumina-magnesia, alumina-baria, alumina-lanthanum oxide, etc., but are not particularly limited thereto. It should be noted that the alumina matrix particles 42 can be used alone or in combination of two or more.
[0055] The average particle size D of the alumina matrix particles 42 50 The average particle size D of the alumina matrix particles 42 can be appropriately set according to the desired performance and is not particularly limited. 50 It is preferably 0.1 μm or more, more preferably 1 μm or more, and even more preferably 3 μm or more. It is preferably 50 μm or less, more preferably 45 μm or less, and even more preferably 40 μm or less.
[0056] Pd is highly dispersed and co-supported on the surface 42a of the alumina matrix particle 42. Here, Pd functions as a catalytically active component. By supporting Pd on the surface 42a of the alumina matrix particle 42, purification performance and low-temperature purification performance can be improved.
[0057] The content ratio of Pd can be appropriately set in consideration of the raw material, pore diameter, etc. of the alumina base material particles 42 and the desired performance, and is not particularly limited. However, from the viewpoint of catalytic activity, etc., the total content of Pd is preferably 0.001 to 5% by mass, more preferably 0.01 to 3% by mass, and further preferably 0.1 to 1% by mass, in terms of metal conversion, relative to the total amount of the second composite catalyst particles 41.
[0058] The second composite catalyst particle 41 may further support a Ba component as an alkaline earth metal on the surface 42a of the alumina base material particle 42. These components are known as NOx storage components. The Ba component may be supported on the surface 42a of the alumina base material particle 42 in the form of, for example, barium carbonate, barium sulfate, etc., and stores NOx in a lean fuel environment with more oxygen, and releases the stored NOx in a rich fuel environment with less oxygen. The content ratio of the Ba component can be appropriately set in consideration of the raw material, pore diameter, etc. of the alumina base material particle 42 and the desired performance, and is not particularly limited. However, from the viewpoint of catalytic activity, etc., it is preferably 0.1 to 10% by mass, more preferably 0.5 to 8% by mass, and further preferably 1 to 5% by mass, based on oxide conversion, relative to the total amount of the second composite catalyst particle 41 (excluding the amount of precious metal).
[0059] The third composite catalyst particles 51 are composite particles having at least ceria alumina matrix particles 52 and Pd supported on surfaces 52a of the ceria alumina matrix particles 52. The third composite catalyst particles 51 may be used alone or in combination of two or more.
[0060] The ceria alumina matrix particles 52 are composite oxides of ceria (CeO2) and alumina (Al2O3). The content ratio of ceria and alumina can be appropriately set according to the desired performance, and is not particularly limited. According to the oxide conversion, the content ratio of ceria:alumina is preferably 10-30 mass %:70-90 mass %, and more preferably 15-25 mass %:75-85 mass %. It should be noted that the ceria alumina matrix particles 52 may contain the above-mentioned rare earth elements, transition elements, alkali metal elements, alkaline earth metal elements, etc. in addition to ceria and alumina. In addition, the ceria alumina matrix particles 52 may be used alone, or two or more may be used in combination as appropriate.
[0061] The average particle size D of the ceria-alumina matrix particles 52 50The average particle size D of the ceria alumina matrix particles 52 can be appropriately set according to the desired performance and is not particularly limited. 50 It is preferably 1 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, and is preferably 30 μm or less, more preferably 20 μm or less, further preferably 15 μm or less.
[0062] Pd is highly dispersed and co-loaded on the surface 52a of the ceria alumina matrix particles 52. Here, Pd functions as a catalytically active component. By loading Pd on the surface 52a of the ceria alumina matrix particles 52, heat resistance and OSC performance can be maintained high, thereby improving purification performance and low-temperature purification performance.
[0063] The content ratio of Pd can be appropriately set in consideration of the raw material, pore diameter, etc. of the ceria-alumina matrix particles 52 and in accordance with the desired performance, and is not particularly limited. However, from the viewpoint of catalytic activity, etc., the total content of Pd is preferably 0.001 to 15% by mass, more preferably 0.1 to 5% by mass, and even more preferably 0.3 to 3% by mass, in terms of metal conversion, relative to the total amount of the third composite catalyst particles 51.
[0064] The fourth composite catalyst particles 61 are composite particles having at least ceria alumina matrix particles 62 and Rh supported on surfaces 62a of the ceria alumina matrix particles 62. The fourth composite catalyst particles 61 may be used alone or in combination of two or more.
[0065] The ceria alumina matrix particles 62 are composite oxides of ceria (CeO2) and alumina (Al2O3). The content ratio of ceria and alumina can be appropriately set according to the desired performance, and is not particularly limited. According to the oxide conversion, the content ratio of ceria:alumina is preferably 10-30 mass %: 70-90 mass %, and more preferably 15-25 mass %: 75-85 mass %. It should be noted that the ceria alumina matrix particles 62 may contain the above-mentioned rare earth elements, transition elements, alkali metal elements, alkaline earth metal elements, etc. in addition to ceria and alumina. In addition, the ceria alumina matrix particles 62 may be used alone, or two or more may be used in combination as appropriate.
[0066] The average particle size D of the ceria-alumina matrix particles 62 50 The average particle size D of the ceria alumina matrix particles 62 can be appropriately set according to the desired performance and is not particularly limited. 50It is preferably 1 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, and is preferably 30 μm or less, more preferably 20 μm or less, further preferably 15 μm or less.
[0067] Rh is highly dispersed and co-loaded on the surface 62a of the ceria alumina matrix particles 62. Here, Rh functions as a catalytically active component. By loading Rh on the surface 62a of the ceria alumina matrix particles 62, it is possible to maintain high heat resistance and OSC performance, and further, it is possible to suppress the reduction of catalytic performance when exposed to high temperatures, thereby improving purification performance and low-temperature purification performance.
[0068] The content ratio of Rh can be appropriately set in consideration of the raw material, pore size, etc. of the ceria alumina matrix particles 62 and in accordance with the desired performance, and is not particularly limited. However, from the viewpoint of catalytic activity, etc., the total content of Rh is preferably 0.001 to 15% by mass, more preferably 0.1 to 5% by mass, and even more preferably 0.3 to 3% by mass, calculated as Rh metal, relative to the total amount of the fourth composite catalyst particles 61.
[0069] In the catalyst layer 21 of the present embodiment, Rh and Pd supported on each composite catalyst particle 31, 41, 51, 61 change to a metal element or a metal oxide according to the external environment. Therefore, Rh and Pd supported on each composite catalyst particle 31, 41, 51, 61 only need to be confirmed at least in a reducing atmosphere, and the properties of Rh and Pd in an oxidizing atmosphere or a stoichiometric atmosphere are not particularly limited to metal elements. Here, in this specification, the so-called reducing atmosphere refers to a state of standing at 400°C for 0.5 hours or more under a hydrogen atmosphere. It should be noted that the presence of Rh and Pd can be determined by various measurement methods such as observation using a scanning transmission electron microscope (STEM), powder X-ray diffraction (XRD), electron probe microanalyzer (EPMA), X-ray photoelectron spectroscopy (XPS, or ESCA), etc.
[0070] The method for producing each composite catalyst particle 31, 41, 51, 61 is not particularly limited as long as it can obtain particles in which Rh, Pd, CeO2 particles 33, and barium components are supported on the surface 32a, 42a, 52a, 62a of each base material particle 32, 42, 52, 62 as described above. From the viewpoint of producing composite particles simply and at low cost, an evaporation-to-drying method (impregnation method) or the like is preferred.
[0071] The matrix particles 32, 42, 52, 62 used as raw materials here can use commercial products of various grades, and can also be manufactured using methods known in the industry. Their manufacturing methods are not particularly limited. For example, the zirconium oxide matrix particles 32 are preferably coprecipitated and alkoxide methods. As a coprecipitation method, for example, the following method is preferably used: to an aqueous solution mixed with cerium salts and / or zirconium salts according to a prescribed stoichiometric ratio, and other rare earth metal elements, transition elements, etc., add an alkaline substance to hydrolyze it or coprecipitate the precursor, and calcine its hydrolyzate or coprecipitate. The types of various salts used here are not particularly limited. Generally, hydrochlorides, oxygen-containing chlorates, nitrates, oxygen-containing nitrates, carbonates, phosphates, acetates, oxalates, citrates, etc. are preferred. In addition, the types of alkaline substances are not particularly limited. Ammonia solution is generally preferred. As an alkoxide method, for example, the following method is preferred: a mixture obtained by mixing cerium alkoxide and / or zirconium alkoxide, and other rare earth metal elements, transition elements, etc. as required in a prescribed stoichiometric ratio is hydrolyzed and then calcined. The type of alkoxide used here is not particularly limited. Usually, methanolate, ethanolate, propoxide, isopropoxide, butoxide, their ethylene oxide adducts, etc. are preferred. In addition, the rare earth metal element can be combined in the form of a metal alkoxide or in the form of the above-mentioned various salts. As far as the calcination conditions are concerned, as long as they are in accordance with conventional methods, there is no particular limitation. The calcination atmosphere can be any atmosphere in an oxidizing atmosphere, a reducing atmosphere, or an atmospheric atmosphere. The calcination temperature and the treatment time vary according to the desired composition and its stoichiometric ratio. From the perspective of productivity, it is usually preferably above 150°C and below 1300°C, 1 to 12 hours, and more preferably above 350°C and below 800°C, 2 to 4 hours. Before the high-temperature calcination, it is preferred to perform reduced-pressure drying using a vacuum dryer or the like, and perform a drying treatment at 50° C. to 200° C. for about 1 to 48 hours.
[0072] As an evaporation-to-drying method, the following method is preferred: an aqueous solution containing ions of Rh, Pd, Ce ions, Ba ions, etc. to be loaded is impregnated into each of the above-mentioned parent material particles 32, 42, 52, 62, and then heat-treated or chemically treated. Through this impregnation treatment, the ions of Rh, Pd, Ce ions, Ba ions, etc. are adsorbed (attached) on the surfaces 32a, 42a, 52a, 62a of each parent material particle 32, 42, 52, 62 in a highly dispersed state. At this time, the ions of Rh and Pd can be combined in the aqueous solution in the form of various salts of Rh and Pd. The types of various salts used here are not particularly limited. Generally, sulfates, hydrochlorides, oxygen-containing chlorates, nitrates, oxygen-containing nitrates, carbonates, oxygen-containing carbonates, phosphates, acetates, oxalates, citrates, chlorides, oxides, composite oxides, complexes, etc. are preferred. In addition, the content ratio of Rh and Pd ions in the aqueous solution can be appropriately adjusted so that Rh and Pd become the desired content ratio in each of the obtained composite catalyst particles 31, 41, 51, 61 or the catalyst layer 21, and is not particularly limited. In addition, it is needless to say that the aqueous solution used here may contain the above-mentioned arbitrary components, such as other rare earth elements, transition elements, and inevitable impurities.
[0073] After the impregnation treatment, solid-liquid separation treatment, water washing treatment, drying treatment (for example, in the atmosphere, at a temperature of about 50°C to about 200°C, the water is removed for about 1 to 48 hours) and the like can be carried out according to conventional methods as needed. The drying treatment can be natural drying, or a drying device such as a drum dryer, a reduced pressure dryer, or a spray dryer can be used. In addition, the atmosphere during the drying treatment can be any atmosphere in the atmosphere, in a vacuum, or in an inert gas atmosphere such as nitrogen. It should be noted that before and after drying, pulverization treatment, classification treatment, etc. can be further carried out as needed. In addition, chemical treatment can be carried out. For example, after the impregnation treatment in the above-mentioned evaporation to dry method, an alkaline component can be used to hydrolyze the ions of Rh and Pd on each of the base material particles 32, 42, 52, and 62. The alkaline component used here is preferably an amine such as ammonia and ethanolamine, an alkali metal hydroxide such as sodium hydroxide and strontium hydroxide, and an alkaline earth metal hydroxide such as barium hydroxide. By these heat treatments and chemical treatments, Rh, Pd, etc., which are highly dispersed in nanometer order, and CeO 2 particles 33 and barium components as required are generated on each of the base material particles 32 , 42 , 52 , 62 .
[0074] As for the firing conditions, it is not particularly limited as long as it is in accordance with conventional methods. The heating means is not particularly limited, for example, known equipment such as an electric furnace and a gas furnace can be used. The firing atmosphere can be any atmosphere of an oxidizing atmosphere, an atmospheric atmosphere, and a reducing atmosphere, preferably an oxidizing atmosphere and an atmospheric atmosphere. The firing temperature and the treatment time vary according to the desired performance. From the viewpoint of the generation and productivity of Rh and Pd, it is usually preferably 300°C to 1100°C, 0.1 to 12 hours, and more preferably 400°C to 800°C, 0.5 to 6 hours.
[0075] As for the catalyst layer 21, in addition to the above-mentioned components, it can be mixed with known catalysts, promoters, parent material particles, etc. in the industry for use. As known catalysts, promoters, and parent material particles that can be used in combination, for example, metal oxides or metal composite oxides such as silica, alumina, lanthanum oxide, neodymium oxide, and praseodymium oxide can be cited; perovskite-type oxides; composite oxides containing alumina such as silica-alumina, silica-alumina-zirconia, and silica-alumina-boria; barium compounds, zeolites, etc., but are not particularly limited thereto. It should be noted that the proportion of the catalysts, promoters, and parent material particles used in combination can be appropriately set according to the required performance, etc., and is not particularly limited. With respect to the total amount, it is preferably 0.01% by mass or more and 20% by mass or less, more preferably 0.05% by mass or more and 10% by mass or less, and further preferably 0.1% by mass or more and 8% by mass or less.
[0076] In addition, as for the catalyst layer 21, in addition to the above-mentioned components, it can also be mixed with additives known in the industry for use. As additives that can be used in combination, various binders, nonionic surfactants, anionic surfactants and other dispersion stabilizers, pH adjusters, viscosity modifiers, etc. can be cited, but they are not particularly limited to this. As binders, various sols such as alumina sol, titania sol, silica sol, and zirconium oxide sol can be cited, but they are not particularly limited to this. In addition, soluble salts such as aluminum nitrate, aluminum acetate, titanium nitrate, titanium acetate, zirconium nitrate, and zirconium acetate can also be used as binders. In addition, acids such as acetic acid, nitric acid, hydrochloric acid, and sulfuric acid can also be used as binders. It should be noted that the amount of binder used is not particularly limited, as long as it is the amount required to maintain the molded body. It should be noted that the use ratio of the above-mentioned additives can be appropriately set according to the required performance, etc., and is not particularly limited. Relative to the total amount, it is preferably 0.01 to 20% by mass, more preferably 0.05 to 10% by mass, and further preferably 0.1 to 8% by mass.
[0077] In the exhaust gas purification catalyst 100 for a saddle-type vehicle of the present embodiment, the above-mentioned catalyst layer 21 is provided on at least one side of the metal substrate 11. By adopting such a structure, a catalyst structure with low manufacturing load and low cost is realized, and it is easy to assemble it into a device during manufacturing, etc., and the applicability to various uses is increased. For example, by using a metal honeycomb structure carrier or the like as the metal substrate 11, the exhaust gas purification catalyst 100 for a saddle-type vehicle is provided in a flow path for air flow to pass through, so that the air flow passes through the holes (cells) of the honeycomb structure carrier, thereby being able to efficiently purify the exhaust gas.
[0078] Here, in this specification, the so-called "single-layer catalyst" refers to a catalyst having only one catalyst layer. In addition, the so-called "arranged on at least one side of the metal substrate 11" includes a mode in which any other layer other than the catalyst layer is interposed between one side of the metal substrate 11 and the catalyst layer.
[0079] Such an exhaust gas purification catalyst 100 for a saddle-riding type vehicle can be obtained, for example, by providing a catalyst layer 21 on the above-mentioned metal substrate 11. As for the method for forming the catalyst layer 21, it can be carried out according to a conventional method without any particular limitation. For example, various known coating methods, wash coat methods, etc. can be applied to apply a slurry mixture of the components of the above-mentioned catalyst layer 21 on the metal substrate 11, and drying, calcining, etc. can be performed as needed, thereby obtaining the exhaust gas purification catalyst 100 for a saddle-riding type vehicle of this embodiment.
[0080] As a specific example, the above-mentioned composite catalyst particles 31, 41, 51, 61, aqueous medium, and binders known in the industry, other catalysts, co-catalysts, OSC materials, various base material particles, additives, etc. used as needed can be mixed in a desired proportion to prepare a slurry mixture, and the obtained slurry mixture can be applied to the surface of the metal substrate 11, dried and sintered, thereby obtaining an exhaust gas purification catalyst 100 for saddle-type vehicles having a catalyst layer 21 provided on the metal substrate 11.
[0081] As for the aqueous medium used when preparing the slurry mixture, the amount of each main component that can be uniformly dispersed in the slurry can be used. At this time, as required, an acid or alkali for adjusting pH can be used, or a surfactant, a dispersion resin, etc. for adjusting viscosity and improving the dispersibility of the slurry can be used. From the viewpoint of making the obtained catalyst layer 21 firmly attached or bonded to the metal substrate 11, it is preferred to use the above-mentioned binder, etc. In addition, as a mixing method for the slurry, a known pulverization method or mixing method such as pulverization mixing performed by a ball mill, etc. can be applied.
[0082] After the slurry mixture is applied to the metal substrate 11, it can be dried and fired according to a conventional method. It should be noted that the drying temperature is not particularly limited, and is preferably 70 to 200° C., and more preferably 80 to 150° C. In addition, the firing temperature is not particularly limited, and is preferably 300 to 650° C., and more preferably 400 to 600° C. The heating means used at this time can be performed using known heating means such as an electric furnace, a gas furnace, etc.
[0083] The total coating amount of the above-mentioned catalyst layer 21 is not particularly limited, but from the viewpoints of catalytic performance, balance of pressure loss, etc., it is preferably 1 to 200 g / L (excluding the amount of precious metal) per 1L capacity of the metal substrate 11, and more preferably 50 to 180 g / L (excluding the amount of precious metal).
[0084] In addition, the total coating amount of Rh and Pd is not particularly limited, but from the viewpoints of catalytic performance, balance of pressure loss, etc., it is preferably 0.05 to 1.5 g / L in metal conversion, and more preferably 0.1 to 1.0 g / L. At this time, the total coating amount of Rh is not particularly limited, but from the viewpoints of catalytic performance, balance of pressure loss, etc., it is preferably 0.02 to 0.6 g / L in metal conversion, and more preferably 0.04 to 0.4 g / L. On the other hand, the total coating amount of Pd is not particularly limited, but from the viewpoints of catalytic performance, balance of pressure loss, etc., it is preferably 0.03 to 0.9 g / L in metal conversion, and more preferably 0.06 to 0.6 g / L. Moreover, the mass ratio of the coating amount of Pd to Rh (Pd / Rh) is preferably 10 / 1 to 10 / 9 in metal conversion, and more preferably 10 / 2 to 10 / 8.
[0085] The exhaust gas purification catalyst 100 for a saddle-riding vehicle of the present embodiment described above can be arranged in the exhaust system of various engines of a saddle-riding vehicle, and the number and location of the installation can be arbitrarily designed according to the restrictions of the exhaust gas. Moreover, the exhaust gas purification catalyst 100 for a saddle-riding vehicle of the present embodiment can exert the following effects: although it is a simple and low-cost structure with only one catalyst layer, it has excellent purification performance of CO, HC, and NOx and low-temperature purification performance.
[0086] Example
[0087] The following examples and comparative examples are given to more specifically illustrate the features of the present invention, but the present invention is not subject to any limitation thereof. That is, the material, usage, ratio, processing content, processing steps etc. shown in the following examples can be appropriately changed, as long as they do not depart from the gist of the present invention. In addition, the values of the various manufacturing conditions and evaluation results in the following examples have the meaning of the preferred upper limit or the preferred lower limit in the embodiment of the present invention, and the preferred numerical range can also be the scope specified by the combination of the aforementioned upper limit or lower limit, the value of the following examples or the values of the examples each other.
[0088] (Example 1)
[0089] Zirconia composite oxide matrix particles containing 75.0 mass % of ZrO2 and 25.0 mass % of oxides of rare earth elements in terms of oxide conversion are placed in a Nautamixer, and a specified amount of cerium nitrate and pure water for dilution are further added, followed by stirring for 15 minutes to prepare composite particles having 12.5 mass % of CeO2 particles in terms of oxide conversion loaded on the surface of the zirconium oxide composite oxide matrix particles.
[0090] Next, a predetermined amount of rhodium nitrate and pure water were added to the stirrer, stirred for 5 minutes, and then the composite particles were added, and further stirred for 15 minutes. Thus, an Rh catalyst slurry containing the first composite catalyst particles in which Rh and CeO2 particles were co-loaded on the surface of the zirconium oxide composite oxide matrix particles was obtained.
[0091] Next, a predetermined amount of palladium nitrate and pure water were added to the stirrer, and after stirring for 5 minutes, ceria alumina matrix particles for the third composite catalyst particles (containing 80.7% by mass of Al2O3 and 19.3% by mass of CeO2 in terms of oxides) were further added, and stirred for 15 minutes. Thus, a Pd catalyst slurry containing the third composite catalyst particles in which Pd was loaded on the surface of the ceria alumina matrix particles was obtained.
[0092] The Rh catalyst slurry and Pd catalyst slurry were weighed in predetermined amounts, put into a stirrer, and stirred for 15 minutes. Then, the mixture was pulverized by a ball mill until the average particle size D90 became 11 μm. An alumina sol-based binder material and distilled water were added to the mixture, and the mixture was further stirred for 10 minutes to obtain a catalyst slurry for a carrier coating.
[0093] Then, a stainless steel metal honeycomb carrier (300 cpsi / 50 μm, 40×90 mmL) was immersed in the carrier coating catalyst slurry, and the excess carrier coating liquid in the pores was removed by blowing, dried, and calcined at 500°C for 1 hour to obtain an exhaust gas purification catalyst for a saddle-type vehicle. The carrier coating amount of the catalyst was 120 g / L (excluding the amount of precious metal) per 1 L of the stainless steel metal honeycomb carrier, the Rh content was 0.2 g / L, and the Pd content was 0.3 g / L.
[0094] (Example 2)
[0095] A prescribed amount of rhodium nitrate and pure water were added to the agitator, and after stirring for 5 minutes, the CeO2 particle-loaded composite particles obtained in Example 1 were added, and further stirred for 15 minutes. Ceria alumina matrix particles (containing 80.7% by mass of Al2O3 and 19.3% by mass of CeO2 in terms of oxide conversion) for the fourth composite catalyst particles were further added thereto, and stirred for 15 minutes. Thus, an Rh catalyst slurry containing the first composite catalyst particles in which Rh and CeO2 particles were co-loaded on the surface of the zirconium oxide composite oxide matrix particles and the fourth composite catalyst particles in which Rh was loaded on the surface of the ceria alumina matrix particles was obtained.
[0096] Next, a predetermined amount of palladium nitrate and pure water were added to the stirrer, and after stirring for 5 minutes, Al2O3 powder with Ba loaded on the surface was added, and further stirred for 15 minutes. Then, 1N nitric acid was added until the pH became 4 to 5, and stirred for 15 minutes. Thus, a Pd catalyst slurry containing second composite catalyst particles with Pd and Ba loaded on the surface of alumina particles was obtained.
[0097] The Rh catalyst slurry and Pd catalyst slurry obtained were weighed in predetermined amounts, respectively, and put into a stirrer. After stirring for 15 minutes, Al2O3 powder with Ba loaded on the surface was further put in and stirred for 15 minutes. Then, the mixture was pulverized by a ball mill until the average particle size D90 became 11 μm. After adding an alumina sol-based binder material and distilled water to the obtained mixture, the mixture was further stirred for 10 minutes, thereby obtaining a catalyst slurry for a carrier coating.
[0098] Then, a stainless steel metal honeycomb carrier (300 cpsi / 50 μm, 40×90 mmL) was immersed in the carrier coating catalyst slurry, and the excess carrier coating liquid in the pores was removed by blowing, dried, and calcined at 500°C for 1 hour to obtain an exhaust gas purification catalyst for a saddle-type vehicle. The carrier coating amount of the catalyst was 120 g / L (excluding the amount of precious metal) per 1 L of the stainless steel metal honeycomb carrier, the Rh content was 0.2 g / L, and the Pd content was 0.3 g / L.
[0099] (Comparative Example 1)
[0100] A prescribed amount of rhodium nitrate and pure water were added to the agitator, stirred for 5 minutes, and then ceria alumina matrix particles were added and stirred for 15 minutes. Thus, a mixed slurry containing composite catalyst particles loaded with Rh on the surface of ceria alumina matrix particles was obtained. Then, the mixed slurry was pulverized by a ball mill until the average particle size D90 became 11 μm. After adding an alumina sol-based binder material and distilled water to the obtained mixture, it was further stirred for 10 minutes to obtain a Rh catalyst slurry containing composite catalyst particles loaded with Rh on the surface of ceria alumina matrix particles.
[0101] Next, a predetermined amount of palladium nitrate and pure water were added to the agitator, stirred for 5 minutes, and then ceria alumina matrix particles were added and stirred for 15 minutes. Thus, a mixed slurry containing composite catalyst particles loaded with Pd on the surface of ceria alumina matrix particles was obtained. Then, the mixed slurry was pulverized by a ball mill until the average particle size D90 became 11 μm. After adding an alumina sol-based binder material and distilled water to the obtained mixture, the mixture was further stirred for 10 minutes to obtain a Pd catalyst slurry.
[0102] Then, after the stainless steel metal honeycomb carrier (300 cpsi / 50 μm, 40×90 mmL) was immersed in the Pd catalyst slurry, the excess carrier coating liquid in the pores was removed by blowing, and the carrier was dried and calcined at 500°C for 1 hour. Then, after the stainless steel metal honeycomb carrier coated with the Pd catalyst slurry was immersed in the Rh catalyst slurry, the excess carrier coating liquid in the pores was removed by blowing, and the carrier was dried and calcined at 500°C for 1 hour to obtain a multilayer catalyst for exhaust gas purification for saddle-type vehicles. The carrier coating amount of the catalyst was 120 g / L (excluding the amount of precious metal) per 1L of the stainless steel metal honeycomb carrier, the Rh content was 0.2 g / L, and the Pd content was 0.3 g / L.
[0103] (Comparative Example 2)
[0104] Specified amounts of the Rh catalyst slurry obtained in Comparative Example 1 and the Pd catalyst slurry obtained in Comparative Example 1 were weighed respectively, put into a stirrer, and after adding an alumina sol-based binder material and distilled water, stirred for 10 minutes, thereby obtaining a catalyst slurry for carrier coating.
[0105] Then, a stainless steel metal honeycomb carrier (300 cpsi / 50 μm, 40×90 mmL) was immersed in the carrier coating catalyst slurry, and the excess carrier coating liquid in the pores was removed by blowing, dried, and calcined at 500°C for 1 hour to obtain an exhaust gas purification catalyst for a saddle-type vehicle. The carrier coating amount of the catalyst was 120 g / L (excluding the amount of precious metal) per 1 L of the stainless steel metal honeycomb carrier, the Rh content was 0.2 g / L, and the Pd content was 0.3 g / L.
[0106] <Performance Evaluation>
[0107] The purification characteristics of each catalyst were evaluated using a model gas evaluation device manufactured by Horiba, Ltd. Here, the reduction ratio of HC, CO and NO (nitrogen oxide) in the model gas at 450°C (C450 purification rate) and the temperature at which the purification rate reaches 50% [T50 (°C)] were measured to evaluate the three-way purification performance of each catalyst. It should be noted that in this evaluation, a punched test piece (25.4×50mmL) of the exhaust gas purification catalyst for saddle-type vehicles obtained from Examples 1 to 2 and Comparative Examples 1 to 2 was kept at 1050°C for 5 hours in an atmosphere in which a rich atmosphere of 2% CO+10% H2O+residue N2 and a lean atmosphere of 5% O2+10% H2O+residue N2 were changed at intervals of 5 minutes each, and the catalysts after durability treatment were used as evaluation samples. In addition, the evaluation device used is a flow-type reaction device composed of stainless steel piping. The model gas of the following composition is introduced from the input side, and it is circulated in the exhaust gas purification reaction part and discharged to the outlet side. The model gas is heated by an external heater and transported to the exhaust gas purification reaction part, thereby heating the purification reaction part. The gas composition on the outflow side (after passing through the catalyst part) is analyzed in the temperature range of 100°C to 450°C to find the change rate of CO, HC and NO concentrations. The results are shown in Figure 6 and Figure 7 .
[0108] Model gas composition: CO: 0.3%, C3H6: 3000ppm, NO: 3000ppm, O2: 0.15%, CO2: 10%, H2O: 10%, N2: the rest
[0109] A / F=14.5
[0110] Space velocity (SV): 72,000 / h
[0111] Evaluation temperature: 100~500℃
[0112] Heating rate: 10℃ / min
[0113] Industrial Applicability
[0114] Although the exhaust gas purification catalyst for saddle-riding type vehicles of the present invention is a simple and low-cost structure having only one catalyst layer, it has excellent purification performance of CO, HC, and NOx and their low-temperature purification performance, and has excellent productivity and economy. Therefore, based on its composition and structure, it can be widely and effectively used as a three-way catalyst (TWC: Three Way Catalyst) for reducing NOx, CO, HC, etc. in exhaust gas. In particular, the exhaust gas purification catalyst for saddle-riding type vehicles of the present invention can be particularly effectively used in the field of two-wheeled vehicles that are small in capacity and require high heat resistance and high exhaust gas purification efficiency even in a fuel-rich atmosphere.
[0115] Description of Reference Numerals
[0116] 100···Exhaust gas purification catalyst for saddle-type vehicles
[0117] 11···Metal substrate
[0118] 21···Catalyst layer
[0119] 31···First composite catalyst particle
[0120] 32···Zirconium oxide matrix particles
[0121] 32a···Surface
[0122] 33···CeO2 particles
[0123] 41···Second composite catalyst particles
[0124] 42···Alumina parent material particles
[0125] 42a···Surface
[0126] 51···The third composite catalyst particle
[0127] 52···Ceria alumina matrix particles
[0128] 52a···Surface
[0129] 61···No. 4 Composite Catalyst Particles
[0130] 62···Cerium dioxide alumina matrix particles
[0131] 62a···Surface
Claims
1. An exhaust gas purification catalyst for a saddle-type vehicle, the exhaust gas purification catalyst for a saddle-type vehicle being provided in an exhaust gas passage of an internal combustion engine, The exhaust gas purification catalyst for a saddle-type vehicle comprises a metal substrate and a single-layer catalyst layer provided on the metal substrate. The catalyst layer contains: a first composite catalyst particle, the first composite catalyst particle comprising at least a zirconia-based matrix particle and Rh and CeO2 particles co-supported on the surface of the zirconia-based matrix particle; and The second composite catalyst particles and / or the third composite catalyst particles, the second composite catalyst particles comprising alumina matrix particles and Pd supported on the surface of the alumina matrix particles, the third composite catalyst particles at least comprising ceria alumina matrix particles and Pd supported on the surface of the ceria alumina matrix particles, wherein: The ceria-alumina matrix particles are composite oxides of ceria and alumina.
2. The exhaust gas purification catalyst for a saddle-rider type vehicle according to claim 1, wherein The zirconia-based matrix particles are rare earth solid solution zirconia matrix particles in which at least one rare earth element selected from the group consisting of Ce, Nd, and La is solid-solved.
3. The exhaust gas purification catalyst for a saddle-rider type vehicle according to claim 1 or 2, wherein The zirconium oxide-based matrix particles contain 65 to 85% by mass of ZrO2 and 15 to 35% by mass of an oxide of a rare earth element in terms of oxide.
4. The exhaust gas purification catalyst for a saddle-rider type vehicle according to claim 1 or 2, wherein The second composite catalyst particles include the alumina base material particles and Pd and Ba supported on the surfaces of the alumina base material particles.
5. The exhaust gas purification catalyst for a saddle-rider type vehicle according to claim 1 or 2, wherein The ceria-alumina matrix particles of the third composite catalyst particles contain 70 to 90% by mass of Al 2 O 3 and 10 to 30% by mass of CeO 2 in terms of oxides.
6. The exhaust gas purification catalyst for a saddle-rider type vehicle according to claim 1 or 2, wherein The catalyst layer further includes fourth composite catalyst particles, and the fourth composite catalyst particles include ceria alumina matrix particles and Rh supported on the surfaces of the ceria alumina matrix particles.
7. The exhaust gas purification catalyst for a saddle-rider type vehicle according to claim 1 or 2, wherein The coating amount of the catalyst layer is 1 to 200 g / L per 1 L of the metal substrate.
Citation Information
Patent Citations
Catalytic material and catalyst for cleaning exhaust gas from internal-combustion engine
JP2010227739A
Exhaust gas-purifying palladium single layer catalyst for saddle-riding type vehicle
JP2013208578A
Alumina material containing barium sulfate and exhaust gas purifying catalyst using same
CN104066507A
Exhaust gas purification palladium monolayer catalyst for saddle-riding-type vehicle
CN104245125A
Exhaust gas purification device
CN108472590A